Decay Resistance of Medium Density Fibreboard (MDF) Made from Pineapple Leaf Fiber - Yuliati Indrayani; Dina Setyawati; Tsuyoshi Yoshimura; Kenji Umemura (Institute for Research and Community Services (LPPM) ITB, 2015)
Medium density fiberboard (MDF) production is increasing due to the development of manufacturing technologies. MDF products are utilized for traditional wood applications that require fungal resistance. This study investigated some of the important biodegradation properties of MDF composite board made from renewable biomass from pineapple leaf fiber (Ananas comosus). The variable factors were type of board and type of resin. Two different types of board with a target density of 0.8 g/cm3 were manufactured. The boards were prepared in three layers of about 1:1:1 weight ratio in crossoriented and unidirectional pattern, using low molecular weight (LM) phenol formaldehyde (PF) resin type PL-3725 and high molecular weight (HM) PF resin type PL-2818 for impregnation and adhesive purposes. Decay resistance (white and brown rot fungi) of the MDF was evaluated to assess its biological performance. In this study, fiber orientation had no effect on the decay resistance to white and brown rot fungi of the specimens. However, a slight increase was found for the mass loss of the low molecular weight PF resin board specimens compared with the mixed low and high molecular PF resin board specimens. The total resin content of 20% of the type I boards prohibits degradation by decay.